Prospects for the Development of Tourism and Hospitality Industry in Uzbekistan - Bekmurodova Laylo Tursunmamatovna (International Journal on Integrated Education, 2022)
In the 21st century, the development of tourism in the world has entered a new stage and is becoming a leading industry of the world economy. Today, tourism is a socio-economic sector of a booming industry in many countries. Today, one of every 16 jobs created in the world is in the tourism business. In the next decade, the tourism industry in European countries and a number of other countries will continue to be a major source of job creation. Since independence, Uzbekistan has set as its main goal to build a society based on a market economy. The tourism sector is also one of the leading sectors in this endeavour. Tourism is not only about exploring the past, getting to know other nations and peoples, enjoying the monuments of their culture, but also big business. Therefore, one of our priorities is to ensure the development of tourism in our country, improve the efficiency and quality of tourism services, and improve the range of services provided by hotel companies in accordance with international standards, the share of tourism in economic growth and the quality of hotel services.